Produccion de yuca en cultivos multiples - Leihner, D.E.; Thung, M.; Cock, James H.; Lynam, John K. (International Center for Tropical Agriculture, 1983)
A detailed review on cassava production in intercropping systems is given, based on the following aspects: selection of plant types for intercropping; realtive planting time, planting density and pattern (spatial arrangement); mineral nutrition and fertilization, competition for nutrients; pest, disease, and weed management, biological potential to reduce weeds, chemical and integrated weed control; evaluation of intercropping systems; economic evaluation. The advantages of intercropping systems are discussed; tables are included on cassava yields obtained in different trials. (CIAT)